Playing Impartial Games on a Simplicial Complex as an Extension of the Emperor Sum Theory: Discrete and Computational Geometry, Graphs, and Games - Suetsugu, Koki (Thai Journal of Mathematics, 2023)
In this paper, we considered impartial games on a simplicial complex. Each vertex of a given simplicial complex acts as a position of an impartial game. Each player in turn chooses a face of the simplicial complex and, for each position on each vertex of that face, the player can make an arbitrary number of moves. Moreover, the player can make only a single move for each position on each vertex, not on that face. We show how the P-positions of this game can be characterized using the P-position length. This result can be considered an extension of the emperor sum theory. While the emperor sum only allowed multiple moves for a single component, this study examines the case where multiple moves can be made for multiple components, and clarifies areas that the emperor sum theory did not cover.